Functional Evaluation of Tryptophans in Glycolipid Binding and Membrane Interaction by HET-C2, a Fungal Glycolipid Transfer Protein - Kenoth, Roopa (Biochim Biophys Acta, 2018)
HET-C2 is a fungal glycolipid transfer protein (GLTP) that uses an evolutionarily-modified GLTP-fold to achieve more focused transfer specificity for simple neutral glycosphingolipids than mammalian GLTPs. Only one of HET-C2’s two Trp residues is topologically identical to the three Trp residues of mammalian GLTP. Here, we provide the first assessment of the functional roles of HET-C2 Trp residues in glycolipid binding and membrane interaction. Point mutants HET-C2(W208F), HET-C2(W208A) and HET-C2(F149Y) all retained >90% activity and 80–90% intrinsic Trp fluorescence intensity; whereas HET-C2(F149A) transfer activity decreased to ~55% but displayed ~120% intrinsic Trp emission intensity. Thus, neither W208 nor F149 is absolutely essential for activity and most Trp emission intensity (~85–90%) originates from Trp109. This conclusion was supported by HET-C2(W109Y/F149Y) which displayed ~8% intrinsic Trp intensity and was nearly inactive. Incubation of the HET-C2 mutants with 1-palmitoyl-2-oleoyl-phosphatidylcholine vesicles containing different monoglycosylceramides or presented by lipid ethanol-injection decreased Trp fluorescence intensity and blue-shifted the Trp λ(max) by differing amounts compared to wtHET-C2. With HET-C2 mutants for Trp208, the emission intensity decreases (~30–40%) and λ(max) blue-shifts (~12 nm) were more dramatic than for wtHET-C2 or F149 mutants and closely resembled human GLTP. When Trp109 was mutated, the glycolipid induced changes in HET-C2 emission intensity and λ(max) blue-shift were nearly nonexistent. Our findings indicate that the HET-C2 Trp λ(max) blue-shift is diagnostic for glycolipid binding; whereas the emission intensity decrease reflects higher environmental polarity encountered upon nonspecific interaction with phosphocholine headgroups comprising the membrane interface and specific interaction with the hydrated glycolipid sugar.